2017
DOI: 10.1371/journal.pone.0174032
|View full text |Cite
|
Sign up to set email alerts
|

Epigenomic annotation of noncoding mutations identifies mutated pathways in primary liver cancer

Abstract: Evidence that noncoding mutation can result in cancer driver events is mounting. However, it is more difficult to assign molecular biological consequences to noncoding mutations than to coding mutations, and a typical cancer genome contains many more noncoding mutations than protein-coding mutations. Accordingly, parsing functional noncoding mutation signal from noise remains an important challenge. Here we use an empirical approach to identify putatively functional noncoding somatic single nucleotide variants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 95 publications
1
6
0
Order By: Relevance
“…Consistent with previous discovery, 25 we found elevated observed/expected values across most tissues analyzed in repressed ChromHMM states, including heterochromatin (13_Het), repressed Polycomb states (17_ReprPCWk) and Quies (18_Quies) (Fig. 4a).…”
Section: Repressed Regions In Normal Mucosa Are Demethylated In Lstsupporting
confidence: 92%
“…Consistent with previous discovery, 25 we found elevated observed/expected values across most tissues analyzed in repressed ChromHMM states, including heterochromatin (13_Het), repressed Polycomb states (17_ReprPCWk) and Quies (18_Quies) (Fig. 4a).…”
Section: Repressed Regions In Normal Mucosa Are Demethylated In Lstsupporting
confidence: 92%
“…In instances where there was insufficient power, for example, rs77325852 with a power of 30.5% for DBP and CADD score of 7.62 in Table , the CADD score indicated that this variant was likely to have causal variation effects. Evidence is mounting that noncoding variants located in DNA regulatory elements, as are all the NOS3 variants that passed multiple testing thresholds in our analyses (Table ), may have functional consequences by creating, deleting, or altering binding sites for transcriptional regulators (Lowdon and Wang ). Indeed, Chip‐seq annotations of NOS3 rs373009, rs867225, and rs77325852 from ENCODE‐based datasets provide strong evidence supporting regulatory effects, however, linking a specific regulatory effect to these polymorphisms is beyond the scope of our investigation.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have reported variants located in intronic and regulatory regions as causative of rare disorders (Johnston et al, 2019; Vuckovic et al, 2020; Whiffin et al, 2020). Moreover, disruption of regulatory mechanisms of gene expression is recognized as an important factor in carcinogenesis (K. Li et al, 2020; Lowdon & Wang, 2017; Orlando et al, 2018; Weinhold et al, 2014). Furthermore, some studies have been able to define tumor subtypes by the recurrent noncoding variants they carry, suggesting the possibility of the use of epigenetic signatures in diagnosis and treatment (Hayward et al, 2017; Torchia et al, 2016; Wellenreuther et al, 1995)…”
Section: Discussionmentioning
confidence: 99%